Can low-carbon city pilot policies improve urban energy efficiency? evidence from a quasi-natural experiment in China - Cheng, Fangfang; Guo, Feng; Tang, Jiaomei; Liu, Junxia (Frontiers in Environmental Science, 2024)
In the context of global efforts to alleviate climate change, this study focuses on investigating the significance and impact of low-carbon city pilot policies (LCCPP), a key strategy in the reduction of greenhouse gas emissions. Drawing on data from prefecture-level cities spanning 2004 to 2019, the study explores the potential of LCCPP in enhancing green total factor energy efficiency (GTFEE) employing a multitemporal Difference-in-Differences (DID) model and examines its transmission mechanisms. First, LCCPP is shown to be effective in enhancing GTFEE. Second, heterogeneity testing indicates that the impact of LCCPP on GTFEE is more pronounced in "two control zones", namely in developing and mature resource cities. Third, industrial restructuring is identified as the key mechanism through which LCCPP influences GTFEE.